Устойчивость стержневых и тонкостенных систем: [учеб. пособие] / В. И. Климанов - Климанов Венедикт Иванович (УПИ, 1988)
Экземпляры: КХ (20110714) / Инвентарный номер: 0286342 / Цена: 0.20 / Сис.шифр: 22.25 / Авт.знак: К 49 / ГРНТИ: 30 / ББК: 22.251.6